2018
DOI: 10.1007/s10886-018-0937-1
|View full text |Cite
|
Sign up to set email alerts
|

Attractiveness of Host Plant Volatile Extracts to the Asian Citrus Psyllid, Diaphorina citri, is Reduced by Terpenoids from the Non-Host Cashew

Abstract: Diaphorina citri is a vector of the bacterial causative agent of Huanglongbing (HLB = Citrus greening), a severe disease affecting citrus crops. As there is no known control for HLB, manipulating insect behaviour through deployment of semiochemicals offers a promising opportunity for protecting citrus crops. The behavioural responses of D. citri to plant volatiles, and the identity of these plant volatiles were investigated. Volatiles were collected from host plants Murraya paniculata, Citrus sinensis, C. resh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
31
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 41 publications
(59 reference statements)
3
31
0
1
Order By: Relevance
“…However, we found higher mean numbers of ACT immature stages (eggs and nymphs), galls and infested leaves on citrumelo than on the other cultivars, which might be partially attributed to volatiles produced by citrumelo. This is consistent with results of Fancelli et al () who demonstrated a positive relationship between host plant volatiles and attraction of D. citri to its preferred host plants. Additional studies to address ACT‐citrumelo volatiles and their attraction are crucial to understanding the underlying mechanisms involved in their preference for feeding and oviposition on this host and for the development of attractants for ACT.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…However, we found higher mean numbers of ACT immature stages (eggs and nymphs), galls and infested leaves on citrumelo than on the other cultivars, which might be partially attributed to volatiles produced by citrumelo. This is consistent with results of Fancelli et al () who demonstrated a positive relationship between host plant volatiles and attraction of D. citri to its preferred host plants. Additional studies to address ACT‐citrumelo volatiles and their attraction are crucial to understanding the underlying mechanisms involved in their preference for feeding and oviposition on this host and for the development of attractants for ACT.…”
Section: Discussionsupporting
confidence: 93%
“…is consistent with results ofFancelli et al (2018) who demonstrated a positive relationship between host plant volatiles and attraction of D. citri to its preferred host plants. Additional studies to address ACT-citrumelo volatiles and their attraction are crucial to understanding the underlying mechanisms involved in their preference for feeding and oviposition on this host and for the development of attractants for ACT.…”
supporting
confidence: 92%
“…However, potential psyllid semiochemicals have been identified, for example, the homoterpenes DMNT and ( E,E )‐4,8,12‐trimethyltrideca‐1,3,7,11‐tetraene (TMTT). A synthetic mixture of DMNT and TMTT reduced the attractiveness of the hosts orange jasmine , Murraya paniculata and sweet orange Pera D6, Citrus sinensis , in a four‐arm olfactometer bioassay . In Y‐shaped and four‐arm olfactometer assays, dimethyl disulfide, identified from the non‐host guava, Psidium guajava , reduced the attractiveness of volatiles from C. sinensis .…”
Section: Possible Application Of Semiochemicals To Whitefly Managementmentioning
confidence: 99%
“…A synthetic mixture of DMNT and TMTT reduced the attractiveness of the hosts orange jasmine, Murraya paniculata and sweet orange Pera D6, Citrus sinensis, in a four-arm olfactometer bioassay. 48 In Y-shaped and four-arm olfactometer assays, dimethyl disulfide, identified from the non-host guava, Psidium guajava, reduced the attractiveness of volatiles from C. sinensis. 49 Furthermore, dimethyl disulfide released from polyethylene vials reduced D. citri infestation in an orchard of Valencia oranges, C. sinensis, for up to 4 weeks.…”
Section: Possible Application Of Semiochemicals To Whitefly Managementmentioning
confidence: 99%
“…Outras linhas de pesquisas desenvolvidas são as relacionadas a substâncias (feromônio e compostos voláteis) que possam atrair (Zanardi et al, 2018;Beloti et al, 2017) ou repelir (Silva et al, 2016;Alquézar et al, 2017;Fancelli et al, 2018) o vetor. Neste sentido, foi isolado o gene de um composto volátil produzido pela goiabeira (β-cariofileno) e utilizado para a transformação genética de Arabidopsis thaliana visando à repelência ao psilídeo (Alquézar et al, 2017).…”
Section: /12unclassified